1984
DOI: 10.1128/iai.44.2.502-507.1984
|View full text |Cite
|
Sign up to set email alerts
|

Naturally occurring pasteurellosis in laboratory rabbits: chemical and serological studies of whole cells and lipopolysaccharides of Pasteurella multocida

Abstract: Whole cells and lipopolysaccharides (LPS) of 10 isolates of Pasteurella multocida from laboratory rabbits were subjected to chemical and serological analysis. LPS of most of these isolates possessed pyrogenic potency comparable to LPS from Salmonella minnesota 9700, although their average ketodeoxyoctonate content was only 18% of that of salmonella. A gel diffusion precipitin test for somatic antigens extracted in a formal-saline solution demonstrated several isolates with three to four somatic antigens, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

1985
1985
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 19 publications
(20 reference statements)
0
15
0
Order By: Relevance
“…Although P. multocida LPS resembles that of smooth enteric bacteria in that they have major chemical components in common (24,31), it is also similar to rough enteric LPS with regard to having lower molecular weight (20) and, in most cases, greater hydrophobicity (31). Increased outer membrane permeability in P. multocida may be due to the LPS being structurally similar to that of rough enteric mutants (31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although P. multocida LPS resembles that of smooth enteric bacteria in that they have major chemical components in common (24,31), it is also similar to rough enteric LPS with regard to having lower molecular weight (20) and, in most cases, greater hydrophobicity (31). Increased outer membrane permeability in P. multocida may be due to the LPS being structurally similar to that of rough enteric mutants (31).…”
Section: Discussionmentioning
confidence: 99%
“…That the atypical permeability properties are due to chemical composition rather than structural anomolies is implicit. The gel diffusion precipitin test developed by Heddleston et al (14) has been used to demonstrate 16 distinguishable serotypes (2, 5) on the basis of the heatstable somatic antigenicity of lipopolysaccharide (LPS) (24,31). Lugtenberg et al (20) have reported the LPS of P. multocida to be of lower molecular weight than that found in certain smooth members of the family Enterobacteriaceae, suggesting fewer repeating sugars and subsequently shorter 0-side-chain length.…”
mentioning
confidence: 99%
“…been widely used for a variety of reasons (3). The indirect hemagglutination assay, one of the more frequently used tests, lacks sensitivity (14). Comparison of the agglutination test and the ELISA for measuring antibody responses in turkeys receiving oral vaccination against P. multocida revealed that the ELISA was more sensitive and correlated with protection against oral challenge with virulent P. multocida (15).…”
Section: Methodsmentioning
confidence: 99%
“…Culture techniques to detect infection are time consuming, and failure to isolate the organisms may be due to their low numbers or inaccessible location rather than to their absence. Although a number of procedures have been developed for the measurement of humoral immunity, recent reports (6,14,15) indicate that antibody detection by the enzyme-linked immunosorbent assay (ELISA) may be more suitable for assessment of pasteurella infection. We therefore explored the use of ELISA for detecting antibodies to P. multocida in naturally infected rabbits.…”
mentioning
confidence: 99%
“…Recently, a few reports concerning antibody production in rabbit pasteurellosis [6,17,19,21,35] have been published. These investigators employed the tube agglutination test using formalinized whole cell antigen [35], the agar gel precipitation test using somatic antigen [19] and the enzyme-linked immunosorbent assay (ELISA) using boiled-cell extract, and appraisable results were obtained by the latter two methods.…”
Section: Serological Examinationmentioning
confidence: 99%